Comparison of the Application of the Brainstorming and Buzz Group Methods to the Knowledge Level of Pregnant Women's Husbands About the Danger Signs of Pregnancy - Rahayu Khairiah; Chica Sumirat (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aims: Maternal mortality in Indonesia is estimated to occur in 20 thousand out of five million births. Health education about danger signs of pregnancy, childbirth and childbirth is important information to be given to husbands of pregnant women. So that this information can be received easily, this information is provided with relaxed techniques and methods, namely brainstorming and buzz groups. Methods: The study was analyzed by unvariate and bivariate dependent t test (Pair test), and displayed in tabular form the husband's knowledge about the dangers of pregnancy before and after being given the Brain Storming Method and the Buzz Group Method as well as the dependent pair test t test Results: Frequency distribution of husbands' knowledge about the dangers of pregnancy after being given the Brain Storming Method at Posyandu Mawar 1-4 in Luhurjaya Village, Lebak Regency with good knowledge is 17 people (56.7%) and those with poor knowledge are 13 people (46.%) ). Frequency distribution of husbands' knowledge about the dangers of pregnancy after being given the Buzz Group Method at Posyandu Mawar 5 – 8 (RW 5 – 8) in Luhurjaya Village, Lebak Regency, there were 22 people (73.3%) who had good knowledge and 8 who had poor knowledge people (26.7%). Conclusion: there is a significant difference between the husband's knowledge about the dangers of pregnancy before the Brain Storming Method and the Buzz Group Method, but statistically the results of the Buzz Group method are better than the Brain Storming Method because the p value is smaller 0.0001 <0.001.